Resin composition, resin coating material, insulated wire, automobile wire harness, and method for producing
By using a combination of α-olefin copolymer, wetting dispersant and antioxidant in the resin coated material of the insulated wire, the problems of insufficient softness and poor manufacturing properties of the insulated wire are solved, and high flexibility and chemical resistance are achieved. It avoids screen clogging in composite manufacturing and improves the overall performance of insulated wires.
Patent Information
- Application Number
- CN202480002595.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-28
- Filing Date
- 2024-02-22
- Publication Date
- 2024-12-20
AI Technical Summary
In electric vehicle applications, existing insulated wires are insufficient in softness and are difficult to take into account both flame retardancy, heat resistance and manufacturing. Especially when low-density polyethylene is used, it is difficult to improve the softness. At the same time, ethylene-based copolymers will increase the softness. Reduce insulation and increase contact wear with metal molds.
The ethylene α-olefin copolymer with 4 to 12 carbon atoms of α-olefin components is used as the base resin, and the wetting dispersant and antioxidant are combined, and the crystallinity and dispersion of the copolymer are adjusted by combining cross-linking additives. , so as to form a resin composition with high flexibility and chemical resistance, and a resin coating material for insulating electric wires to avoid clogging of screens during composite production.
On the basis of maintaining the excellent characteristics of the existing resin coating materials, the softness and chemical resistance of the insulated wires are significantly improved, ensuring excellent composite manufacturing, avoiding screen clogging, and improving the overall performance of the insulated wires.
Smart Images

Figure BDA0005128055970000191 
Figure BDA0005128055970000201
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, a resin coating material, an insulated electric wire, a wiring harness for an automobile, and a method for producing the wiring harness for an automobile. Background Art
[0002] Insulated wires with flame retardancy are widely used in various white appliances, OA equipment, etc. In addition, insulated wires used in automobiles, etc. are also required to have various properties such as flame retardancy or heat resistance, softness (flexibility), and mechanical properties. To date, many resin compositions have been studied and reported for achieving insulated wires with flame retardancy or heat resistance, softness (flexibility), and mechanical properties by using them as a covering material for conductors.
[0003] For example, Patent Document 1 describes an insulating resin composition that can form an insulating layer having excellent flexibility and high tensile strength. In addition, when an adhesive is used for end water stopping, the insulating layer has excellent adhesion to the adhesive, and the pull-out force is stable. The insulating resin composition contains: a resin component; and 30 to 100 parts by mass of a flame retardant and 1 to 5 parts by mass of a crosslinking aid relative to 100 parts by mass of the resin component, wherein the resin component contains: a first copolymer, which is a copolymer of an unsaturated hydrocarbon having 4 or more carbon atoms and ethylene; a second copolymer, which is a copolymer of an unsaturated hydrocarbon having 4 or more carbon atoms and ethylene, which is acid-modified and has a density of less than 0.88 g / cm 3 and a third copolymer, which is a copolymer of acrylic acid ester and ethylene, wherein the content ratio of the first copolymer to the third copolymer is within a specific range.
[0004] Patent Document 2 describes a resin composition having sufficient flexibility and heat resistance as a coating layer of an electric wire. The resin composition contains: a resin component including an ethylene-(meth)acrylate copolymer, an ethylene-propylene-diene terpolymer, and at least one of an ethylene-acrylate rubber; and a flame retardant, wherein the resin component is cross-linked.
[0005] Patent Document 3 describes a heat-resistant resin composition that has excellent high-temperature heat resistance, high flexibility and oil resistance, and no problem with the appearance of the resin after extrusion, so it can be used in rubber insulated flexible cables, etc. The heat-resistant resin composition contains specific amounts of components (A) to (E). Specifically, it contains: Component (A): The density before silane modification is 0.850 to 0.900 g / cm 3, silane-modified polyethylene and silane-modified ethylene-α-olefin copolymer, which is 10 to 80% by mass relative to the total of components (A) to (D); component (B) polyolefin resin, which is 3 to 60% by mass relative to the total of components (A) to (D); component (C) at least one of a styrene-based elastomer and an ethylene-α-olefin copolymer rubber, which is 10 to 50% by mass relative to the total of components (A) to (D); component (D) paraffin oil, which is 5 to 60% by mass relative to the total of components (A) to (D); component (E) silanol condensation catalyst, which is 0.005 to 0.5 part by mass relative to 100 parts by mass of the total of components (A) to (D).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2018-012817
[0009] Patent Document 2: Japanese Patent Application Publication No. 2020-105319
[0010] Patent Document 3: Japanese Patent Application Publication No. 2014-009238 Summary of the invention
[0011] Problems to be solved by the invention
[0012] In recent years, the world is rapidly developing environmentally responsive vehicles, centered around electric vehicles (EVs). In particular, as the diameter of wires increases, the insulating coating material is required to be more flexible due to the large current, ease of wiring, and space saving of hybrid and electric vehicles. In order to impart flexibility to the insulating coating material, low-density polyethylene with a density of 0.910 or more and less than 0.930 has been used as a resin material. However, it is difficult to impart higher flexibility to the insulating coating material in the case of low-density polyethylene.
[0013] In addition, although the flexibility of ethylene-vinyl acetate copolymer (EVA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methyl acrylate copolymer (EMA), ethylene-butyl acrylate copolymer (EBA) and other ethylene copolymers can be improved by increasing the amount of copolymer monomer components, the insulation properties are reduced due to the increase in the proportion of polar components. In addition, the adhesion with metal is improved, which increases the contact wear with the metal mold during extrusion processing, and as a result, the appearance and manufacturability of the manufactured product may be damaged.
[0014] Furthermore, in order to further improve flame retardancy and heat resistance, fillers such as flame retardants and antioxidants are highly compounded. However, fillers with small particle sizes are easily reagglomerated, and clogging of the screen is easily caused when the compound is produced using a feed extruder or a twin-screw extruder.
[0015] In view of the above situation, the subject of the present invention is to provide a resin composition, which can fully maintain the excellent properties (insulation, processability, flame retardancy, heat resistance, cold resistance, mechanical properties, etc.) of existing resin coating materials by forming an insulating film (resin coating material layer) for insulated wires, and further improve the softness (flexibility) of the insulated wires, can improve chemical resistance (oil resistance), and thus have excellent composite manufacturability (not prone to clogging of the mesh). In addition, the subject of the present invention is to provide a resin coating material using the above resin composition, an insulated wire having a layer of the resin coating material, an automotive wiring harness containing the insulated wire, and a method for manufacturing the same.
[0016] Means for solving problems
[0017] The inventors of the present invention have conducted research to solve the above-mentioned problems, and have found that in a resin composition for insulating coating materials using an ethylene-α-olefin copolymer having 4 to 12 carbon atoms as a base resin, by making the crystallinity of the copolymer within a specific range, mixing a specific amount of a wetting dispersant, and then mixing an antioxidant and a crosslinking aid, the resin composition can be made more flexible and chemically resistant while fully maintaining the excellent properties of existing resin coating materials. Furthermore, the dispersibility of fillers can be improved by the action of the wetting dispersant, and in the manufacture of a composite using the resin composition, clogging of a screen in a feed extruder or a twin-screw extruder can be suppressed (excellent composite manufacturability). The present invention was completed by further repeated research based on these insights.
[0018] That is, the above-mentioned problems are solved by the following means.
[0019] <1>
[0020] A resin composition comprising the following components (A) to (D),
[0021] (A) a base resin of an ethylene-α-olefin random copolymer having 4 to 12 carbon atoms and containing an α-olefin component;
[0022] (B) wetting and dispersing agents;
[0023] (C) antioxidants;
[0024] (D) a cross-linking aid;
[0025] The ethylene-α-olefin random copolymer having 4 to 12 carbon atoms in the α-olefin component has a crystallinity of 15% to 24%.
[0026] The content of the component (B) is 2 to 10 parts by mass based on 100 parts by mass of the component (A).
[0027] <2>
[0028] As mentioned above <1> The resin composition contains a softener as component (E).
[0029] <3>
[0030] As mentioned above <2> The resin composition, wherein the component (E) is a chain hydrocarbon polymer and / or a hindered amine compound.
[0031] <4>
[0032] As mentioned above <1> ~ <3> The resin composition described above, wherein the component (A) contains at least one of a styrene-based elastomer, an ethylene-propylene rubber, and an olefin-based block copolymer.
[0033] <5>
[0034] As mentioned above <1> ~ <4> The resin composition described in any one of the above, wherein the content of the component (C) is 10 to 30 parts by mass relative to 100 parts by mass of the content of the component (A).
[0035] <6>
[0036] As mentioned above <1> ~ <5> The resin composition described above, wherein the content of the component (D) is 0.5 to 6 parts by mass relative to 100 parts by mass of the content of the component (A).
[0037] <7>
[0038] As mentioned above <1> ~ <6> The resin composition described above is used for forming a resin coating material for an insulated electric wire constituting an automobile wiring harness.
[0039] <8>
[0040] A resin-coated material, which is <1> ~ <7> Obtained by crosslinking any one of the resin compositions.
[0041] <9>
[0042] An insulated wire, wherein the insulating film has the above <8> The resin coating material.
[0043] <10>
[0044] A wiring harness for an automobile, comprising the above <9> The insulated wire.
[0045] <11>
[0046] A method for manufacturing a wiring harness for an automobile, comprising the following steps: extruding a coating on a conductor <1> ~ <7> A layer of the resin composition is formed by using any one of the resin compositions, and the layer of the resin composition is irradiated with electron beams of 80 kGy to 250 kGy.
[0047] Effects of the Invention
[0048] The composite of the resin composition of the present invention has excellent manufacturability, and by forming an insulating film (resin coating material layer) for an insulated wire, an insulated wire having excellent flexibility and excellent chemical resistance can be obtained while fully maintaining the excellent properties of the existing resin coating material. The automotive wiring harness of the present invention has the above-mentioned resin coating material in the insulating film of the insulated wire, and has excellent flexibility and excellent chemical resistance (oil resistance). According to the manufacturing method of the automotive wiring harness of the present invention, an automotive wiring harness having the above-mentioned excellent properties or advantages can be obtained. DETAILED DESCRIPTION
[0049] [Resin composition]
[0050] The resin composition of the present invention contains (A) a base resin of an ethylene-α-olefin random copolymer having 4 to 12 carbon atoms containing an α-olefin component (also referred to as component (A)), (B) a wetting and dispersing agent (also referred to as component (B)), an antioxidant (C) (also referred to as component (C)) and a crosslinking aid (D) (also referred to as component (D)). It should be noted that, in the present invention, "containing components (A) to (D)" and "blended components (A) to (D)" have the same meaning. In addition, in the present invention, unless otherwise stated, the term "resin" is used as a concept including elastomers (i.e., resin and / or elastomer).
[0051] Components (A) to (D) and optional components described below may be used alone or in combination of two or more.
[0052] Hereinafter, the components contained in the resin composition of the present invention will be described.
[0053] <(A) Base resin>
[0054] The resin composition of the present invention comprises a base resin (hereinafter also referred to as "base resin") of an ethylene·α-olefin random copolymer (hereinafter also referred to as "ethylene·α-olefin copolymer") containing an α-olefin component having 4 to 12 carbon atoms. From the perspective of further improving chemical resistance, the content of the ethylene·α-olefin copolymer in the base resin is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more. In addition, all base resins may be ethylene·α-olefin copolymers.
[0055] The remainder of the base resin other than the ethylene·α-olefin copolymer may contain other polymers described later.
[0056] ((A1) Ethylene-α-olefin random copolymer having 4 to 12 carbon atoms in the α-olefin component)
[0057] In the present invention, the α-olefin in the above-mentioned component (A1) is not particularly limited as long as the number of carbon atoms is 4 to 12, and examples thereof include 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, or 1-dodecene. Component (A1) may have a third component other than the ethylene component and the α-olefin component within a range that does not impair the effects of the present invention.
[0058] The crystallinity of the component (A1) is 15% to 24%. From the perspective of improving chemical resistance, the crystallinity is preferably 16% or more, more preferably 17% or more, and further preferably 18% or more. In addition, from the perspective of improving flexibility, the crystallinity is preferably 23% or less, and more preferably 22% or less.
[0059] In the resin composition of the present invention, the crystallinity of the component (A1) is the crystallinity of the component (A1) to be blended.
[0060] In addition, in the present invention, the crystallinity refers to the crystallinity of the above-mentioned component (A1) as a whole. That is, when two or more ethylene α-olefin copolymers are used as the above-mentioned component (A1), the above-mentioned crystallinity is the crystallinity of the two or more ethylene α-olefin copolymers as a whole. In addition, the crystallinity of the component (A1) as a whole can be calculated based on the crystallinity of the ethylene α-olefin copolymers mixed and their mixing amounts. For example, when an ethylene α-olefin copolymer with a crystallinity of 10% and an ethylene α-olefin copolymer with a crystallinity of 30% are mixed in a ratio of 7:3, the crystallinity of the component (A1) as a whole can be calculated as [10%×0.7+30%×0.3=16%].
[0061] The above-mentioned component (A1) is preferably a component consisting of a mixture of two or more copolymers. For example, it is preferred to mix an ethylene α-olefin copolymer (component (A2)) having a crystallinity of 10% to 24% and an ethylene α-olefin copolymer (component (A3)) having a crystallinity of more than 24% and less than 35%, and adjust the crystallinity of the component (A1) consisting of the obtained mixture to be 15% to 24%. In this case, when the total amount of component (A1) is 100 parts by mass, it is preferred that the component (A2) is 60 to 100 parts by mass, the component (A3) is 0 to 40 parts by mass, more preferably the component (A2) is 60 to 80 parts by mass, the component (A3) is 20 to 40 parts by mass, and further preferably the component (A2) is 70 to 80 parts by mass, and the component (A3) is 20 to 30 parts by mass.
[0062] The crystallinity of component (A1) can be determined by obtaining the endothermic peak area (J) using a differential scanning calorimeter by a conventional method and calculating the heat of fusion (J / g) from the endothermic peak area (J) and the sample amount (g). In this case, the crystallinity (%) can be determined by the following (Formula 1).
[0063] Crystallinity (%) = (heat of fusion / heat of fusion of complete crystal) × 100 (Formula 1)
[0064] The measurement conditions using the differential scanning calorimeter are nitrogen atmosphere (nitrogen flow rate: 50 mL / min), and the heating and cooling rates are set to 10°C / min. In addition, the above-mentioned "complete crystal melting heat" can use a known value. For example, the data of TA Instrument can be used. In addition, for resins whose "complete crystal melting heat" is unknown, the complete crystal melting heat of high-density polyethylene "293 J / g" is used as the complete crystal melting heat of the resin to calculate the crystallinity. As the above-mentioned differential scanning calorimeter, for example, DSC6200 (trade name) manufactured by Hitachi High-Technologies Corporation can be used.
[0065] When a commercially available product is used as the component (A1), the value of the crystallinity described in the catalogue can be adopted as the crystallinity of the component (A1).
[0066] In addition, the density of the component (A1) is preferably 0.865 g / cm 3 ~0.880g / cm 3 .
[0067] The above-mentioned component (A1) can be synthesized by a conventional method, and commercial products can also be used. Specific examples of commercial products include ENGAGE 7467 (trade name, ethylene-butene polyolefin elastomer, manufactured by The Dow Chemical Company), ENGAGE 8150 (trade name, ethylene-octene polyolefin elastomer, manufactured by The Dow Chemical Company), and ENGAGE 8452 (trade name, ethylene-octene polyolefin elastomer, manufactured by The Dow Chemical Company).
[0068] (Other polymers)
[0069] The base resin may contain other polymers as polymers other than component (A1) within a range not impairing the effects of the present invention. Examples of such other polymers include at least one of styrene elastomers, ethylene-propylene rubbers, and olefin block copolymers.
[0070] The above-mentioned styrene-based elastomer is a copolymer block derived from the constituent components of an aromatic vinyl compound and a conjugated diene compound and / or a block copolymer or a random copolymer mainly composed of constituent components derived from the above-mentioned compounds. As the aromatic vinyl compound, for example, one or more kinds can be selected from styrene, α-methylstyrene, vinyltoluene, p-tert-butylstyrene, etc., among which styrene is preferred. As the conjugated diene compound, for example, one or more kinds can be selected from butadiene, isoprene, 1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, etc., among which butadiene, isoprene or a combination thereof is preferred.
[0071] As the styrene-based elastomer, a binary or ternary copolymer composed of a polystyrene block and an elastomer block having a polyolefin structure can be used.
[0072] The styrene-based elastomer preferably contains 10% by mass to 70% by mass of a constituent component derived from an aromatic vinyl compound. This content can be determined, for example, by measuring a UV absorption spectrum with an ultraviolet spectrophotometer using a chloroform solution.
[0073] Examples of commercially available styrene-based elastomers include "SEPTON" (trade name, brand name: 4033, type: SEEPS, styrene content: 30%, manufactured by Kuraray Co., Ltd.).
[0074] In the present invention or this specification, the above-mentioned EPDM rubber includes, in addition to ethylene-propylene binary copolymer, ethylene-propylene-diene terpolymer, etc., olefin-based thermoplastic elastomers containing these substances as main components (polyolefins such as polypropylene and polyethylene are used as hard segments, and rubber components such as EPDM rubber are used as soft segments, and the hard segments and soft segments have a microphase-separated structure), etc.
[0075] Examples of commercially available products of the ethylene-propylene-diene copolymer include EP123 (trade name, ENB content: 4.5%, ethylene content: 58%, manufactured by ENEOS MATERIALS).
[0076] The hardness (durometer A) of the olefin-based thermoplastic elastomer is preferably 80 or less. Commercially available products of such elastomers include, for example, MILASTOMER (registered trademark, product number: 4010NS, hardness (durometer A): 46, manufactured by Mitsui Chemicals, Inc.). The hardness (durometer A) is determined by a method in accordance with ISO 7619-2010.
[0077] The above-mentioned olefin block copolymer is a copolymer in which two polyolefins are alternately formed in a block form in one molecule. For example, an olefin block copolymer composed of an amorphous ethylene-octene block (soft) having a high comonomer content and a low glass transition temperature, and a crystallizable ethylene-octene block (hard) having a very low comonomer content and a high melting point can be cited.
[0078] The density of the olefin-based block copolymer is preferably 0.89 g / cm 3 In addition, the melting point is preferably 130°C or less. Examples of commercially available products of such olefin-based block copolymers include INFUSE 9107 (trade name, olefin-based block copolymer (density 0.866 g / cm 3 ), melting point: 121°C, manufactured by Dow Chemical Company).
[0079] From the perspective of further improving flexibility, the content of the other polymer in component (A) is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more. In addition, from the perspective of chemical resistance and crosslinking properties, it is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less.
[0080] <(B) Wetting and dispersing agent>
[0081] The resin composition of the present invention contains (B) a wetting dispersant. A wetting dispersant refers to an additive that has both the function of a wetting material that acts as a surfactant to improve the wettability of the dispersoid to the resin component, and the function of preventing the agglomeration of the dispersoid through electrical repulsion or steric hindrance. Usually, the function of the wetting material is assumed by a chain that is compatible with the resin component, and the function of preventing the agglomeration of the dispersoid is assumed by an adsorptive group to the dispersoid. By making the resin composition of the present invention contain a specific amount of a wetting dispersant, the dispersibility of the mixed filler (such as the flame retardant described later) can be improved, and the composite manufacturability of the resin composition can be improved. As a wetting dispersant, there are liquid or powdered (or flaky) dispersants. From the perspective of workability, a powdered (or flaky) dispersant is preferred. In addition, a dispersant with a dropping point of 50°C or more and a melting point of 100°C or less is preferred.
[0082] In the present invention, a commercially available wetting and dispersing agent can be used as the component (B). Examples of commercially available products include BYK-MAX D4221 and BYK-MAX P4102 (both trade names, manufactured by BYK Chemical Japan Co., Ltd.).
[0083] As described above, the resin composition of the present invention contains 2 to 10 parts by mass of the component (B) relative to 100 parts by mass of the component (A). From the perspective of suppressing the generation of clogging and coagulation protrusions, and suppressing the generation of blooming and cross-linking hindrance, the resin composition of the present invention contains preferably 3 to 9 parts by mass of the component (B) relative to 100 parts by mass of the component (A), more preferably 4 to 8 parts by mass, and even more preferably 5 to 7 parts by mass.
[0084] <(C) Antioxidant>
[0085] The resin composition of the present invention contains (C) an antioxidant. Examples of such component (C) include phenol compounds (phenolic antioxidants), imidazole compounds (imidazole antioxidants), and thioether compounds (thioether antioxidants), and one or more of these may be used.
[0086] From the perspective of improving heat resistance, the resin composition of the present invention preferably contains 10 to 30 parts by mass of component (C) (the total amount of antioxidants when the resin composition contains multiple antioxidants), and more preferably 14 to 22 parts by mass, relative to 100 parts by mass of component (A).
[0087] (Phenolic antioxidant)
[0088] Examples of the phenolic antioxidants that can be used in the resin composition of the present invention include triethylene glycol-bis(3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate), 1,6-hexanediol-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), pentaerythritol-tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1,3,5-trimethyl-2,4,6-tris(3,5,-di-tert-butyl-4-hydroxyphenyl) propionate, Among them, from the aspect of imparting high heat resistance to the wiring harness for automobiles, those having two or more 3,5-di-tert-butyl-4-hydroxyphenyl groups or 3,5-di-tert-butyl-4-hydroxybenzyl groups are preferred, and tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate and pentaerythritol-tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) are particularly preferred.
[0089] In the present invention, a commercially available phenolic antioxidant can be used. Examples of commercially available products include Irganox 1010 (trade name, manufactured by BASF Corporation).
[0090] When the resin composition of the present invention contains a phenolic antioxidant, the content of the phenolic antioxidant is preferably 1 to 8 parts by mass, more preferably 2 to 6 parts by mass, based on 100 parts by mass of the component (A), from the viewpoint of improving heat resistance.
[0091] (Imidazole antioxidant)
[0092] Examples of the imidazole antioxidant that can be used in the resin composition of the present invention include 2-sulfanylbenzimidazole, 2-sulfanylmethylbenzimidazole, 4-sulfanylmethylbenzimidazole, 5-sulfanylmethylbenzimidazole, and zinc salts thereof. 2-sulfanylbenzimidazole and zinc salts thereof are preferred.
[0093] In the present invention, commercially available imidazole antioxidants can be used. Examples of commercially available antioxidants include NOCRACMBZ (trade name, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.).
[0094] When the resin composition of the present invention contains an imidazole antioxidant, the imidazole antioxidant is preferably contained in an amount of 8 to 16 parts by mass, more preferably 10 to 14 parts by mass, based on 100 parts by mass of component (A) from the viewpoint of improving heat resistance.
[0095] (Thioether antioxidant)
[0096] Examples of the thioether antioxidants that can be used in the resin composition of the present invention include dilauryl 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, distearyl 3,3'-thiodipropionate, 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthiopropionate] (also known as bis[3-(dodecylthio)propionic acid] 2,2-bis[[3-(dodecylthio)-1-oxopropyloxy]methyl]-1,3-propanediyl), etc. Among these, 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthiopropionate] is preferred from the viewpoint of improving long-term thermal stability and extraction resistance.
[0097] The resin composition of the present invention can use a commercially available thioether antioxidant, and examples of commercially available antioxidants include ADKSTAB AO-412S (trade name, manufactured by ADEKA Corporation).
[0098] When the resin composition of the present invention contains a thioether antioxidant, the thioether antioxidant is preferably contained in an amount of 0.5 to 4 parts by mass, more preferably 1 to 3 parts by mass, based on 100 parts by mass of component (A) from the viewpoint of improving heat resistance.
[0099] <(D) Cross-linking aid>
[0100] The resin composition of the present invention contains (D) a crosslinking aid. Component (D) includes polyfunctional compounds, preferably compounds having two or more (preferably three or more, more preferably 3 to 6) ethylenically unsaturated bonds (carbon-carbon double bonds) in the molecule.
[0101] Specific examples of the component (D) include (meth)acrylate compounds such as polypropylene glycol diacrylate and trimethylolpropane triacrylate, allyl compounds such as triallyl cyanurate, maleimide compounds, and divinyl compounds.
[0102] In the present invention, a commercially available crosslinking aid can be used as the component (D). Examples of commercially available products include Ogmont T200 (trade name, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.).
[0103] From the perspective of improving heat resistance and chemical resistance, the resin composition of the present invention preferably contains 0.5 to 6 parts by mass of component (D) relative to 100 parts by mass of component (A), more preferably 1 to 5 parts by mass, and even more preferably 2 to 4 parts by mass.
[0104] <Other ingredients>
[0105] In addition to the above components (A) to (D), the resin composition of the present invention may contain other components such as the following softeners, flame retardants, processing aids, additives, etc. within a range that does not inhibit the effects of the present invention.
[0106] <(E) Softener>
[0107] The resin composition of the present invention preferably contains (E) a softener. As the component (E) that can be used in the present invention, a softener that is liquid at room temperature (25° C.) and atmospheric pressure (0.1 MPa) among softeners commonly used for insulating coating materials can be used. Component (E) can be used alone or in combination of two or more.
[0108] Examples of the component (E) include cycloparaffinic or aromatic process oils, chain hydrocarbon polymers, hindered amine compounds, phthalic acid derivatives such as dioctyl phthalate or dibutyl phthalate, white oil, mineral oil, etc. Among them, the component (E) is preferably a chain hydrocarbon polymer and / or a hindered amine compound.
[0109] Examples of the chain hydrocarbon polymer include polybutene, polybutadiene, polyisoprene, and polyisoprene-butadiene copolymers, among which polybutene is preferred.
[0110] The number average molecular weight of the chain hydrocarbon polymer is preferably 300 or more, more preferably 900 or more. In addition, the number average molecular weight is preferably 10,000 or less, more preferably 5,000 or less, more preferably 4,000 or less, and further preferably 3,500 or less. The number average molecular weight is preferably 300 to 10,000, more preferably 300 to 5,000, further preferably 900 to 4,000, and further preferably 900 to 3,500.
[0111] As the hindered amine compound, the NH type in which the imino group (>NH) of the piperidine ring is kept as NH, the N-methyl type in which H is substituted by a methyl group, and the NOR (alkoxyimino) type hindered amine compound having an N-alkoxy (>N-OR) structure are preferred. By having such a structure, flame retardancy can be imparted to the resin composition. As a specific example of the NOR type hindered amine compound, for example, bis (1-undecyloxy-2,2,6,6-tetramethylpiperidin-4-yl) carbonate can be cited.
[0112] In the present invention, a commercially available softener can be used as the component (E). Examples of commercially available softeners include polybutene HV-100 and polybutene HV-1900 manufactured by ENEOS and ADKSTAB FP-T80 manufactured by ADEKA.
[0113] When the resin composition of the present invention contains component (E), from the perspective of further improving chemical resistance and further improving flexibility, relative to 100 parts by mass of component (A), it is preferred to contain 9 parts by mass or more of component (E), more preferably 10 parts by mass or more, more preferably 12 parts by mass or more, and more preferably 14 parts by mass or more. In addition, from the perspective of improving chemical resistance, relative to 100 parts by mass of component (A), it is preferred to contain 21 parts by mass or less of component (E), more preferably 20 parts by mass or less, further preferably 19 parts by mass or less, and further preferably 18 parts by mass or less. If the content of the above-mentioned component (E) relative to 100 parts by mass of component (A) is shown in a preferred range, it is 9 parts by mass to 21 parts by mass, more preferably 10 parts by mass to 20 parts by mass, further preferably 12 parts by mass to 19 parts by mass, and further preferably 14 parts by mass to 18 parts by mass.
[0114] <Flame retardant>
[0115] The present invention may contain a flame retardant within a range that does not impair the effect exerted by the present invention. As such flame retardants, for example, brominated flame retardants and antimony flame retardants can be cited. The present invention preferably contains at least one of a brominated flame retardant or an antimony flame retardant, and more preferably contains a brominated flame retardant and an antimony flame retardant together. In addition, regarding the mixing ratio of the brominated flame retardant and the antimony flame retardant, in terms of the molar ratio of the bromine element to the antimony element, it is preferably within the range of 2 to 5 times the molar amount of bromine relative to the antimony element contained in the resin composition. That is, relative to the molar content of the antimony flame retardant, a brominated flame retardant containing 2 to 5 times the molar amount of bromine is preferably used.
[0116] When the resin composition of the present invention contains a flame retardant, it is preferred that the total amount of the flame retardant be 33 to 45 parts by mass based on 100 parts by mass of the component (A).
[0117] (Brominated flame retardants)
[0118] The above-mentioned bromine-based flame retardant is preferably a bromine-containing compound. That is, the resin composition of the present invention preferably contains a bromine-containing compound as a flame retardant. As a bromine-based flame retardant, for example, brominated N,N'-ethylenebisphthalimide or compounds derived therefrom (these are collectively referred to as "brominated N,N'-ethylenebisphthalimide compounds"), N,N'-bis(bromophenyl)terephthalamide or compounds derived therefrom (these are collectively referred to as "N,N'-bis(bromophenyl)terephthalamide compounds"), brominated bisphenol or compounds derived therefrom (these are collectively referred to as "brominated bisphenol compounds"), 1,2-bis(bromophenyl)alkane and other organic bromine-containing flame retardants can be used. Among them, for example, brominated N,N'-ethylenebisphthalimide and / or 1,2-bis(pentabromophenyl)ethane are preferably used.
[0119] By using brominated N,N′-ethylenebisphthalimide and / or 1,2-bis(bromophenyl)alkane as a flame retardant, a resin coating material that does not substantially cause bleeding can be formed.
[0120] As the brominated flame retardant used in the resin composition of the present invention, a commercially available brominated flame retardant can be used. Examples of commercially available products include SAYTEX 8010 (trade name, manufactured by Albemarle Corporation).
[0121] When the resin composition of the present invention contains a brominated flame retardant, the brominated flame retardant is preferably contained in an amount of 15 to 35 parts by mass based on 100 parts by mass of the component (A).
[0122] (Antimony flame retardant)
[0123] As antimony flame retardants, for example, antimony trioxide, antimony tetroxide, antimony pentoxide, and sodium antimonate can be cited. It is believed that the reaction of antimony with chlorine (halogen) shields oxygen due to the generated gas, thereby promoting the formation of a carbonized layer and capturing free radicals (thermal decomposition chain reaction stops the action). Among them, antimony trioxide is preferably contained in the present invention from the aspect of forming a more stable carbonized layer.
[0124] In the present invention, commercially available antimony trioxide can be used. Examples of commercially available products include PATOX-C (trade name, manufactured by Nippon Seiko Co., Ltd.).
[0125] When the resin composition of the present invention contains an antimony-based flame retardant, it is preferred that the antimony-based flame retardant be contained in an amount of 5 to 15 parts by mass based on 100 parts by mass of the component (A).
[0126] (Other flame retardants)
[0127] In addition to the above-mentioned bromine flame retardant and antimony flame retardant, the resin composition of the present invention may also contain a flame retardant that can be generally used for the insulating film of the insulated wire. As such a flame retardant, metal hydroxides such as magnesium hydroxide and aluminum hydroxide (hydroxide-based flame retardant) can be cited. When the resin composition of the present invention includes a hydroxide-based flame retardant, relative to 100 parts by mass of the content of component (A), it is preferred to contain less than 5 parts by mass of the hydroxide-based flame retardant, and more preferably less than 3 parts by mass.
[0128] <Processing aids>
[0129] The resin composition of the present invention also preferably contains a processing aid within a range that does not impair the effects exerted by the present invention. Preferred examples of the processing aid include metal soaps (lubricants).
[0130] Examples of the metal soap (lubricant) that can be used in the resin composition of the present invention include calcium stearate, zinc stearate, and magnesium stearate.
[0131] In the present invention, commercially available metal soaps can be used. Examples of commercially available metal soaps include SHINACALEAD ZS-101 (trade name, manufactured by Shinagawa Chemical Industry Co., Ltd.).
[0132] When the resin composition of the present invention contains a metal soap, it is preferred that the metal soap be contained in an amount of 0.5 to 2 parts by mass based on 100 parts by mass of the component (A).
[0133] <Additives>
[0134] The resin composition of the present invention may be appropriately blended with various additives such as copper inhibitors, ultraviolet absorbers, dispersants (dispersants other than wetting dispersants), plasticizers, fillers, pigments, etc. as needed within the range that does not impair the effects of the present invention. Examples of such additives include zinc compounds. Specific examples of zinc compounds include zinc sulfide and zinc oxide.
[0135] [Method for producing resin composition]
[0136] The resin composition of the present invention can be obtained by blending the above components (A) to (D) and the above optional components as required, and melt-kneading them using a batch mixer such as a roll, kneader, or Banbury mixer, or a commonly used kneading device such as a twin-screw extruder.
[0137] [Automotive wiring harness]
[0138] The automotive wiring harness of the present invention comprises an insulated wire having a layer of a resin coating material formed by crosslinking the resin composition of the present invention on the surface of a conductor (including a conductor bundle and a fiber core wire). It should be noted that in the automotive wiring harness of the present invention, the insulated wire may have an intermediate layer or a shielding layer between the layer consisting of the conductor and the resin coating material.
[0139] Hereinafter, the automotive wiring harness may be simply referred to as a "wiring harness".
[0140] [Manufacturing method of automobile wiring harness]
[0141] The automotive wiring harness of the present invention can be obtained by the following steps: extrusion coating the resin composition of the present invention on a conductor to form a layer of the resin composition, and irradiating the layer of the resin composition with 80 kGy to 250 kGy of electron beams. By the electron beam irradiation, a crosslinking reaction occurs in the layer of the resin composition to form a resin coating material layer. The wiring harness can be obtained by bundling insulated wires having conductors and their resin coating layers and installing connectors at the ends.
[0142] The conductor may be a single wire or a stranded wire, and may be a bare wire, or may be a tin-plated or enameled wire. Examples of the metal material forming the conductor include soft copper, copper alloy, aluminum, etc. The thickness of the layer formed around the conductor made of the resin coating material is not particularly limited, but is generally about 0.15 mm to 5 mm.
[0143] There are no particular restrictions on the conductor diameter or the material of the conductor, the thickness of the coating layer, etc., and they can be appropriately determined according to the purpose or use. The cross-linking reaction using electron beam irradiation can be carried out using conventional methods and conditions without limitation. Regarding the irradiation conditions of electron beams, the irradiation amount is preferably 50kGy to 450kGy, more preferably 80kGy to 250kGy, further preferably 80kGy to 200kGy, and particularly preferably 80kGy to 160kGy. In addition, the acceleration voltage is preferably 300keV to 5000keV, more preferably 500keV to 3000keV.
[0144] Alternatively, a multilayer structure may be adopted in which an intermediate layer or a shielding layer is provided between the conductor and the coating layer or between the coating layers.
[0145] The conditions for extrusion molding the resin composition of the present invention are not particularly limited as long as the resin composition of the present invention can be extruded. However, from the perspective of reducing the load on the extruder (extrusion molding machine) and ensuring shape retention, the extrusion temperature (head) is preferably 100°C to 230°C, more preferably 120°C to 200°C.
[0146] In addition, other conditions of extrusion molding can be appropriately set according to the purpose.
[0147] The screw structure of the extruder is not particularly limited, and a common full-flight screw, double-flight screw, front double-flight screw, Maddock screw, etc. can be used.
[0148] Example
[0149] The present invention will be described in further detail based on the following Examples and Comparative Examples, but the present invention is not limited thereto.
[0150] [Examples 1 to 12 and Comparative Examples 1 to 5]
[0151] Materials used for preparing the resin compositions of Examples 1 to 12 and Comparative Examples 1 to 5 are shown in the following Table 1. Details of the materials used are as follows.
[0152] <Materials used>
[0153] (Component (A): base resin)
[0154] -Component (A1): Ethylene·α-olefin copolymer-
[0155] ENGAGE 7467: Trade name, ethylene-butene polyolefin elastomer (crystallinity 12%, density 0.862 g / cm 3 ), manufactured by The Dow Chemical Company
[0156] ENGAGE 8150: Trade name, ethylene-octene polyolefin elastomer (crystallinity 16%, density 0.868 g / cm 3 ), manufactured by The Dow Chemical Company
[0157] ENGAGE 8100: Trade name, ethylene-octene polyolefin elastomer (crystallinity 18%, density 0.870 g / cm 3 ), manufactured by The Dow Chemical Company
[0158] ENGAGE 8452: Trade name, ethylene-octene polyolefin elastomer (crystallinity 20%, density 0.875 g / cm 3 ), manufactured by The Dow Chemical Company
[0159] ENGAGE 7256: Trade name, ethylene-octene polyolefin elastomer (crystallinity 23%, density 0.885 g / cm 3 ), manufactured by The Dow Chemical Company
[0160] ENGAGE 8003: Trade name, ethylene-octene polyolefin elastomer (crystallinity 25%, density 0.885 g / cm 3 ), manufactured by The Dow Chemical Company
[0161] ENGAGE 8440: Trade name, ethylene-octene polyolefin elastomer (crystallinity 27%, density 0.897 g / cm 3 ), manufactured by The Dow Chemical Company
[0162] ENGAGE 8480: Trade name, ethylene-octene polyolefin elastomer (crystallinity 33%, density 0.902 g / cm 3 ), manufactured by The Dow Chemical Company
[0163] -Other polymers-
[0164] SEPTON: Trade name, brand name 4033, type SEEPS, styrene content 30%, manufactured by Kuraray
[0165] EP123: Trade name, ENB content 4.5%, ethylene content 58%, manufactured by ENEOS MATERIALS
[0166] MILASTOMER: Registered trademark, product number 4010NS, hardness (durometer A) 46, manufactured by Mitsui Chemicals
[0167] INFUSE 9107: Trade name, olefin block copolymer (density 0.866 g / cm 3 ), melting point 121°C, manufactured by Dow Chemical Company
[0168] (Component (B): wetting and dispersing agent)
[0169] BYK-MAX D4221: Trade name, manufactured by BYK Chemical Japan Co., Ltd.
[0170] (Ingredient (C): Antioxidant)
[0171] Phenolic antioxidant: pentaerythritol-tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), phenolic antioxidant, Irganox 1010 (trade name), manufactured by BASF
[0172] Imidazole antioxidant: zinc salt of 2-mercaptobenzimidazole, NOCRAC MBZ (trade name), manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0173] Thioether antioxidant: 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthiopropionate], ADKSTAB AO-412S (trade name), manufactured by ADEKA Corporation
[0174] (Component (D): cross-linking aid)
[0175] Multifunctional polymer: trimethylolpropane trimethacrylate, Ogmont T200 (trade name), manufactured by Shin-Nakamura Chemical Industry Co., Ltd.
[0176] (Ingredient (E): softener)
[0177] Polybutene HV-100: trade name, polybutene (number average molecular weight: 980), manufactured by ENEOS
[0178] Polybutene HV-1900: trade name, polybutene (number average molecular weight: 2900), manufactured by ENEOS
[0179] ADKSTAB FP-T80: trade name, bis(1-undecyloxy-2,2,6,6-tetramethylpiperidin-4-yl) carbonate, manufactured by ADEKA Corporation
[0180] (Flame Retardant)
[0181] Brominated flame retardant: 1,2-bis(pentabromophenyl)ethane, SAYTEX 8010 (trade name), manufactured by Albemarle
[0182] Antimony: Antimony trioxide, PATOX-C (trade name), manufactured by Nippon Seiko Co., Ltd.
[0183] (Processing Aids)
[0184] Metal soap: Zinc stearate, SHINACALEAD ZS-101 (trade name), manufactured by Shinagawa Chemical Co., Ltd.
[0185] <Preparation of Resin Composition Pellets>
[0186] The composition shown in Table 1 below was melt-kneaded at 180°C using a 75-liter Banbury mixer, and the discharged mixture (compound) was passed through a screen (mesh size: 200 mesh) of an extruder to granulate to obtain resin composition pellets.
[0187] [Performance evaluation]
[0188] The following performance evaluation was performed on each of the resin compositions (Examples 1 to 12 and Comparative Examples 1 to 5) produced as described above.
[0189] <Compound Manufacturing Evaluation>
[0190] When producing the resin composition pellets, the presence or absence of screen replacement accompanied by clogging or the like was evaluated based on the following evaluation criteria.
[0191] -Evaluation Criteria-
[0192] ⊚: Even when 4 batches of 200 kg or more were produced, the resin composition pellets could be produced without replacing the screen.
[0193] ○: The screen did not need to be replaced until the first batch of 50 kg was produced, but the screen was replaced until the fourth batch of 200 kg was produced.
[0194] ×: The screen was replaced until one batch of 50 kg was produced.
[0195] <Evaluation of Flexibility (Flexural Rigidity)>
[0196] Using an extruder set at a temperature of 90°C to 190°C, the obtained resin composition pellets were extruded and coated on a copper conductor (twist number 19 / single wire number 26 / single wire diameter 0.32 mm). The formed resin composition layer was cross-linked by electron beam irradiation. In this way, a copper conductor with a cross-sectional area of 40 mm was obtained. 2An insulated wire (about 12.0 mm in finished outer diameter) having an insulating film with a thickness of 1.4 mm around a conductor made of copper (≈40 sq). It should be noted that crosslinking by electron beams was performed under the conditions of an accelerating voltage of 3000 keV and 160 kGy.
[0197] The flexibility (bending rigidity) evaluation method is measured by the method according to Japanese Industrial Standard JIS C6870-1-21: 2018, Item 19 E17C. Each of the above-mentioned insulated wires (samples) is cut into a length of 400 mm, and a cable (insulated wire) bent to 180 degrees is placed between parallel plates. The ends of the cable are fixed to parallel plates, and a force sensor is placed on the plates to measure the maximum load (N) when bent to a bending interval of 100 mm. The obtained maximum load is evaluated based on the following evaluation criteria.
[0198] It should be noted that the zero point adjustment of the force sensor was performed before the specimen was installed, and the test was carried out at room temperature.
[0199] -Evaluation Criteria-
[0200] ◎: Maximum load is less than 15N
[0201] 0:Maximum load is 15N or more and less than 20N
[0202] ×: Maximum load is 20N or more
[0203] <Gasoline swelling resistance evaluation>
[0204] Using an extruder set at a temperature of 90°C to 190°C, each resin composition pellet obtained was made into a resin sheet with a thickness of 1.4 mm, and subjected to a crosslinking reaction by electron beam irradiation. The resin sheet was punched into a dumbbell sheet with a length of 15 mm and a width of 30 mm as a test piece, and immersed in gasoline for 20 hours at a temperature of 23±5°C. The thickness change rate of the sheet after 30 minutes of removal was measured by the following (Formula 2), and evaluated according to the following evaluation criteria.
[0205] Change rate (%) = {(test piece thickness after immersion - test piece thickness before immersion) / test piece thickness before immersion} × 100 (Formula 2)
[0206] -Evaluation Criteria-
[0207] ◎: Change rate is less than 5%
[0208] ○: Change rate is 5% or more and less than 10%
[0209] ×: Change rate is 10% or more
[0210] The obtained results are shown in the following Table 1. The compounding amounts in the following table are expressed in parts by mass (mass ratio).
[0211]
[0212] [Table 1-2]
[0213] [Table 1] (Continued)
[0214]
[0215]
[0216] The content of each component in the table is parts by mass. Blank columns and "-" mean that the corresponding component is not included.
[0217] As can be seen from Table 1, the resin compositions whose crystallinity of component (A1) is outside the specified range of the present invention (Comparative Examples 1 and 4) and the resin compositions whose content of component (B) is outside the specified range of the present invention (Comparative Examples 2 to 5) are inferior in at least one of the softness evaluation, gasoline swelling resistance evaluation, and composite manufacturability evaluation.
[0218] In contrast, all the resin compositions satisfying the requirements of the present invention (Examples 1 to 12) were evaluated as excellent in flexibility, excellent in gasoline swelling resistance, and excellent in composite manufacturability. It should be noted that these resin compositions have sufficient insulation, flame retardancy, durability, mechanical properties, etc. as resin coating materials for insulated wires.
[0219] The present invention has been described in conjunction with its embodiments, but the applicant believes that, unless otherwise specified, the present invention is not limited to any details in the description and should be broadly interpreted without violating the spirit and scope of the invention as shown in the appended claims.
[0220] This application claims priority based on Japanese Patent Application No. 2023-050983 filed in Japan on March 28, 2023, the contents of which are incorporated herein by reference as a part of the contents described in this specification.
Claims
1. A resin composition comprising the following components (A) to (D), (A) a base resin of an ethylene-α-olefin random copolymer having 4 to 12 carbon atoms and containing an α-olefin component; (B) wetting and dispersing agents; (C) antioxidants; (D) a cross-linking aid; The ethylene·α-olefin random copolymer having 4 to 12 carbon atoms in the α-olefin component has a crystallinity of 15% to 24%. The content of the component (B) is 2 to 10 parts by mass based on 100 parts by mass of the component (A).
2. The resin composition according to claim 1, comprising a softening agent as a component (E).
3. The resin composition according to claim 2, wherein The component (E) is a chain hydrocarbon polymer and / or a hindered amine compound.
4. The resin composition according to any one of claims 1 to 3, wherein The component (A) contains at least one of a styrene-based elastomer, an ethylene-propylene rubber, and an olefin-based block copolymer.
5. The resin composition according to any one of claims 1 to 4, wherein The content of the component (C) is 10 to 30 parts by mass based on 100 parts by mass of the component (A).
6. The resin composition according to any one of claims 1 to 5, wherein The content of the component (D) is 0.5 to 6 parts by mass based on 100 parts by mass of the component (A). 7 . The resin composition according to claim 1 , which is used to form a resin coating material for an insulated electric wire constituting an automobile wiring harness. 8 . A resin-coated material obtained by crosslinking the resin composition according to claim 1 .
9. An insulated wire, wherein: The insulating film comprises the resin coating material according to claim 8 . 10 . A wiring harness for an automobile, comprising the insulated electric wire according to claim 9 . 11 . A method for producing an automobile wire harness, comprising the steps of: extrusion coating a conductor with the resin composition according to claim 1 to form a layer of the resin composition, and irradiating the layer of the resin composition with electron beams of 80 kGy to 250 kGy.
